Visual media processing using MATLAB beginner's guide : learn a range of techniques from enhancing and adding artistic effects to your photographs, to editing and processing your videos, all using MATLAB /: learn a range of techniques from enhancing and adding artistic effects to your photographs, to editing and processing your videos, all using MATLAB. (2013) - Unknown
No abstract available